SARM1 Depletion Slows Axon Degeneration in a CNS Model of Neurotropic Viral Infection - Crawford, Colin L.; Antoniou, Christina; Komarek, Lina; Schultz, Verena; Donald, Claire L.; Montague, Paul; Barnett, Susan C.; Linington, Christopher; Willison, Hugh J.; Kohl, Alain; Coleman, Michael P.; Edgar, Julia M. (Frontiers in Molecular Neuroscience, 2022)
Zika virus (ZIKV) is a neurotropic flavivirus recently linked to congenital ZIKV syndrome in children and encephalitis and Guillain-Barré syndrome in adults. Neurotropic viruses often use axons to traffic to neuronal or glial cell somas where they either remain latent or replicate and proceed to infect new cells. Consequently, it has been suggested that axon degeneration could represent an evolutionarily conserved mechanism to limit viral spread. Whilst it is not known if ZIKV transits in axons, we previously reported that ZIKV infection of glial cells in a murine spinal cord-derived cell culture model of the CNS is associated with a profound loss of neuronal cell processes. This, despite that postmitotic neurons are relatively refractory to infection and death. Here, we tested the hypothesis that ZIKV-associated degeneration of neuronal processes is dependent on activation of Sterile alpha and armadillo motif-containing protein 1 (SARM1), an NADase that acts as a central executioner in a conserved axon degeneration pathway. To test this, we infected wild type and Sarm1 homozygous or heterozygous null cell cultures with ZIKV and examined NAD+ levels as well as the survival of neurons and their processes. Unexpectedly, ZIKV infection led to a rapid SARM1-independent reduction in NAD+. Nonetheless, the subsequent profound loss of neuronal cell processes was SARM1-dependent and was preceded by early changes in the appearance of -tubulin III staining. Together, these data identify a role for SARM1 in the pathogenesis of ZIKV infection, which may reflect SARM1’s conserved prodegenerative function, independent of its NADase activity.